2022
DOI: 10.3389/fpsyg.2022.905590
|View full text |Cite
|
Sign up to set email alerts
|

Regional Entrepreneurship, Business Environment, and High-Quality Economic Development: An Empirical Analysis of Nine Urban Agglomerations in China

Abstract: The article selects socioeconomic data related to 146 prefecture-level cities included in nine city clusters from 2014 to 2018 to establish a city-level socioeconomic system in China. A sensitivity analysis of regional entrepreneurship and economic quality development based on system dynamics was conducted to explore the changes in regional entrepreneurship and economic quality development over time and their sensitivity factors. In this way, the dynamic evolution mechanism of the system can be portrayed, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Companies in the local area gain advantages from FDI in the initial stages of the innovation process, and the effects are more pronounced among firms that innovate by utilizing knowledge rather than creating knowledge. Liu et al [27] also investigated the impact of FDI on regional innovation and the underlying mechanisms in China by using a "spatial autoregressive model" and a "threshold regression model" on a panel dataset of 253 cities spanning from 2003 to 2017. The results indicated that FDI significantly influences regional innovation and generates positive spillovers among cities.…”
Section: Introductionmentioning
confidence: 99%
“…Companies in the local area gain advantages from FDI in the initial stages of the innovation process, and the effects are more pronounced among firms that innovate by utilizing knowledge rather than creating knowledge. Liu et al [27] also investigated the impact of FDI on regional innovation and the underlying mechanisms in China by using a "spatial autoregressive model" and a "threshold regression model" on a panel dataset of 253 cities spanning from 2003 to 2017. The results indicated that FDI significantly influences regional innovation and generates positive spillovers among cities.…”
Section: Introductionmentioning
confidence: 99%
“…The entrepreneurship developed by these breeders is related to a sustainable environment. Based on the results of (Guo et al, 2022) businesses based on highquality environmental and economic development are more prevalent in central cities than in cluster cities. The development of regional entrepreneurship and the development of economic quality turned out to be running asymmetrically.…”
Section: Marketing Guarantee For Its Productsmentioning
confidence: 99%
“…The business environment policy's implementation effect in developed cities is more pronounced [23]. The high-quality urban development of cities is influenced by national and urban agglomeration heterogeneity [24].…”
Section: Studies On the Business Environmentmentioning
confidence: 99%
“…Finally, the business environment as a whole is associated with technological progress. And the ability of cities to innovate is significantly enhanced by the business environment [24]. Improving the business environment contributes to better capital allocation of funding to innovative initiatives and better industry-specific innovation [42,43].…”
Section: The Relationship Between Business Environment and Enterprise...mentioning
confidence: 99%